Key Factors in the Continuance of Self-Service Technology and Its Mobile App Adoption—A Case Study of Convenience Stores in Taiwan - Chun-Hua Hsiao; Kai-Yu Tang (Applied Sciences)
Past literature has advocated the integration of channels through the offline-to-online and online-to-offline models. However, little research has investigated the interrelationships effects between the two channels. Drawing on the literature from self-service technology (SST) and expectation–confirmation theory, this study aims to investigate key attributes of SST and assess their impact on consumer evaluations across offline-to-online and online-to-offline channels. A questionnaire survey was administered at convenience stores and 360 user responses were collected through a physical self-service kiosk. Two-stage structural equation modeling with linear structural relations (LISREL version 8.54) software was used for data analysis. The empirical results verified the attributes of physical SST (physical system’s service quality and perceived convenience) and online SST (virtual system’s service quality and perceived ubiquity) as critical antecedents of satisfaction and attitude and the subsequent behavioral intentions toward each channel. However, some transitional effects from offline (physical kiosk use) to online (kiosk app adoption) intention were not as significant as hypothesized. The offline attributes of perceived convenience and satisfaction had no significant impact on online SST significantly (kiosk app), except for the physical system’s service quality. Discussions and implications are provided, including strategies for concise functional design and essential SST services.